2009
DOI: 10.1519/jsc.0b013e3181b73cb3
|View full text |Cite
|
Sign up to set email alerts
|

Are Anthropometric, Flexibility, Muscular Strength, and Endurance Variables Related To Clubhead Velocity in Low- And High-Handicap Golfers?

Abstract: The present study assessed the anthropometric profile (International Society for the Advancement of Kinanthropometry protocol), flexibility, muscular strength, and endurance of 20 male golfers. These data were collected in order to determine: a) the relationship between these kinanthropometric measures and clubhead velocity; and b) if these measures could distinguish low-handicap (LHG) and high-handicap (HHG) golfers. Ten LHG (handicap of 0.3 +/- 0.5) and 10 HHG (handicap of 20.3 +/- 2.4) performed 10 swings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 20 publications
4
98
2
1
Order By: Relevance
“…The current study reported high reliability in the range of field tests used and statistical significance with CHS in all performance measures apart from LLCMJ. By comparison, lower levels of reliability have been reported in previous work (37) and a range of other studies assessing physical relationships with CHS did not report reliability statistics for the physical performance tests (15,19). The medicine ball rotational throw used in the current study displayed high reliability (ICC = 0.90) and this is comparable to other work using the same test (14).…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…The current study reported high reliability in the range of field tests used and statistical significance with CHS in all performance measures apart from LLCMJ. By comparison, lower levels of reliability have been reported in previous work (37) and a range of other studies assessing physical relationships with CHS did not report reliability statistics for the physical performance tests (15,19). The medicine ball rotational throw used in the current study displayed high reliability (ICC = 0.90) and this is comparable to other work using the same test (14).…”
Section: Resultscontrasting
confidence: 61%
“…An established method of measuring golf driving performance has been to determine the magnitude of club head speed (8,10,14,19,20),which is dependent on many factors including the amount and direction of ground reaction force produced (1), and the use of the kinetic chain sequencing (34).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fradkin et al (2004) established that clubhead velocity was correlated (r = 0.950) with golf handicap (clubhead velocity = 4.065 − 0.0214 x hcp) for 45 male golfers (18-80 years, 2-27 hcp). Further, Keogh et al (2009) found that low handicap golfers (hcp = 1.3 ±0.5) had significantly greater 5-iron accuracy and clubhead velocity and were stronger in the golf swing-specific cable woodchop than the high-handicappers (hcp = 20.3 ±2.4).…”
Section: Organismic Constraints -Golfer Characteristics (Age Gendermentioning
confidence: 92%